A quantitative analysis of tariffs across U.S. states - Ana Maria Santacreu; Michael Sposi; Jing Zhang (Federal Reserve Bank of Chicago, 2021)
We develop a quantitative framework to assess the cross-state implications of a U.S. trade policy change: a unilateral increase in the import tariff from 2% to 25% across all goods-producing sectors. Although the U.S. gains overall from the tariff increase, we find the impact differs starkly across locations. Changes in real consumption (welfare) range from as high as 3.8% in Wyoming to -0.3% in Florida, depending mainly on how exposed states are to differentially-impacted sectors. As a result, the "preferred" tariff rate varies greatly across states. Foreign retaliation in trade policy substantially reduces the welfare gains across states, while perpetuating the cross-state variation in those gains. The presence of internal trade frictions amplifies the welfare impacts of changes in trade policy.
Keywords: F11; F62; 330; International trade; Interstate trade; Welfare gains from trade